Pengaruh Model Self Regulated Learning dan Discovery Learning terhadap Kemampuan Berpikir Kreatif Matematis - Andriyani, Emi; Muhaimin, Muhaimin; Syaiful, Syaiful (Edumatica : Jurnal Pendidikan Matematika, 2021)
This study aims to determine the effect of self-regulated learning (SRL) and discovery learning models on students' mathematical creative thinking abilities, the influence of self-confidence on the ability to think creatively mathematically, and the interaction between the SRL learning model and discovery learning with students' confidence in creative thinking skills. The research method used is a quasi-experimental method. The research sample consisted of 32 people in the experimental class I, 32 people in the experimental class II, and 32 people in the control class. Data collection is done by giving a questionnaire and written test questions. The data analysis used is a two-way ANOVA technique. The results showed the SRL model was more effective in influencing creative thinking skills than the discovery learning model and the conventional model. High and moderate self-confidence of students is more effective in influencing creative thinking skills than low self-confidence. There is an interaction between the SRL and DL models with self-confidence in influencing creative thinking skills.